Evaluation of the effect of Gastoxin® B57 on maize seed quality by germination and cold test - Ferreira, Matheus Kevin Lima; Mello, Marcos Vinicius Moraes; Brito, Raimundo Filho Freire de; Freire, Ana Izabella; Souza, Alex Fernandes de; Cruz, Renata Ranielly Pedroza; Souza, Filipe Bittencourt Machado de; Araújo, Nicolas Oliveira de; Pereira, Matheus Costa; Carmelossi, Michele de Santana (Seven Editora, 2024)
Gastoxin® B57 is used to control stored grain pests. The objective of this study was to evaluate the effect of different doses of Gastoxin® B57 on seed quality of 18 maize lines through germination and cold testing. The seeds were treated with Gastoxin® B57 for 72 hours in a 1m3 environment. The dosages used were: dosage recommended by the manufacturer; twice the recommended dosage and control. After treatment with the insecticide, germination and cold tests were performed. The experimental design was randomized blocks in a 3x18 factorial scheme (3 doses and 18 strains), followed by Tukey's test of comparison of means. Analysis of variance showed that there was a difference in treatments as a function of the doses. Lines 2, 3, 4, 14 and 16 showed higher germination and vigor potentials. The dose recommended by the manufacturer and the control did not affect the seed quality of the corn lines in the cold test and in the germination test. DOI:https://doi.org/10.56238/sevened2023.001-022